FIXED ASSET MANAGEMENT ACCOUNTABILITY OF BATU CITY GOVERNMENT:........ - Wijayanti, Rosari Luhlike; Sukoharsono, Eko Ganis; Hari, Bambang (The International Journal of Accounting and Business Society, 2016)
The aim of this study is to describe and to analyze the accountability of Batu City Government’s fixed asset management. The objects of this study are concerned with the activities of Batu City Government’s fixed asset management centralized in BPKAD (regional institution of finance and asset management). Fixed asset management accountability in this study is concerned with legal and regulatory accountability, process accountability, program accountability, and policy accountability. It is a case study with Stewardship Theory as its analytical instrument. On the Stewardship theory, there are two values: a value of intrinsic and extrinsic. At the Batu City Government, the regional asset management scheme favors to the intrinsic value that are motivated to self-actualization and awards as it is compared with extrinsic values that is motivated to the monetary value. Nevertheless, Stewardship behavior has not underlined that all behaviors and activities are undertaken by the regional government so that the accountability that is achieved has not maximized yet. The results of this study on legal accountability show that 71% of the land assets have not possessed evidences of legal ownership yet. The process accountability, of the majority of the 13 asset management activities, has not possessed a SOP or groove established procedure as regional regulations so that the activities have only been carried out based the existing regulations. On the program and policy accountability that the government produced, Batu City Government has not consistently run the activities in accordance with the program set on RPJMP (government’s mid-term development plan), strategic plan and implementation of policies, and working plan. It has not been conducted maximally in accordance with the existing regulations.